Trust and Normative Control in Multi-Agent Systems - Joana Urbano (2012)
Despite relevant insights from socio-economics, little research in multi-agentsystems has addressed the interconnections between trust and normative notionssuch as contracts and sanctions. Focusing our attention on scenarios of betrayal,in this paper we combine the use of trust and sanctions in a negotiation process.We describe a scenario of dyadic relationships between truster agents,which make use of trust and/or sanctions, and trustee agents, characterized bytheir ability and integrity, which may influence their attitude toward betrayal.Both agent behavior models are inspired in socio-economics literature. Throughsimulation, we show the virtues and shortcomings of using trust, sanctions, anda combination of both in processes of selection of partners.